Renal function and symptoms/adverse effects in opioid‐treated patients with cancer. Issue 8 (5th May 2015) - Kurita, G. P.; Lundström, S.; Sjøgren, P.; Ekholm, O.; Christrup, L.; Davies, A.; Kaasa, S.; Klepstad, P.; Dale, O.
<x xml:space="preserve">Abstract</x> Background Renal impairment and the risk of toxicity caused by accumulation of opioids and/or active metabolites is an under‐investigated issue. This study aimed at analysing if symptoms/adverse effects in opioid‐treated patients with cancer were associated with renal function. Methods Cross‐sectional multicentre study (European Pharmacogenetic Opioid Study, 2005–2008), in which 1147 adult patients treated exclusively with only one of the most frequently reported opioids (morphine/oxycodone/fentanyl) for at least 3 days were analysed. Fatigue, nausea/vomiting, pain, loss of appetite, constipation and cognitive dysfunction were assessed (EORTC QLQ‐C30). Glomerular filtration rate (GFR) was estimated using Cockcroft–Gault (CG), Modification of Diet in Renal Disease (MDRD), and Chronic Kidney Disease Epidemiology Collaboration (CKD‐EPI Creatinine) equations. Results Mild to severe low GFR was observed among 40–54% of patients. CG equation showed that patients with mild and moderate/severe low GFR on morphine treatment had higher odds of having severe constipation (P < 0.01) than patients with normal GFR. In addition, patients with moderate/severe low GFR on morphine treatment were more likely to have loss of appetite (P = 0.04). No other significant associations were found. Conclusion Only severe constipation and loss of appetite were associated with low GFR in patients treated with morphine. Oxycodone and fentanyl, in relation to the symptoms studied, seem to be safe as used and titrated in routine cancer pain care.